New records of scarabaid white grub species and diptrean genus in sugar cane soil in Upper Egypt (Coleoptera: Scarabidae) - Abd-Rabou, S.; Abd-El-Samea, Saadia. A. (2006)
The present work deals with the survey of the soil fauna on sugar cane in Upper Egypt.
Includes references.
Summary in Arabic.
1
Keywords: Sugarcane -- Soils; Sugarcane -- Diseases and pests; White-grub.; Coleoptera